Pelaksanaan Pendidikan Tanggap Budaya di Ruang Kelas Bagi Anak-anak - Jayanti, Gita Dwi; Aulia Inayah, Risma; Lailatul Amanah, Isti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to examine culturally responsive education in the classroom for children, this study was conducted with a literature review. The process of introducing culture to children is an important thing that must be done so that children can accept and understand the diversity that exists. Cultural responsive education will make children love their nation and country more. When children are familiar with the existing culture, they are expected to be able to deal with conflicts that occur as early as possible. When at school or in a classroom of course there are many student with different characters and cultures. Student who have understood the differences will certainly respect each other. Cultural diversity will make life much more beautiful and enjoyable. We can learn from each other about cultures that we didn't know before. Because of this, culturally responsive education really needs to be taught to children.